Teaching Learning Based Algorithm for calculating optimal values of Sensing error probability, Throughput and Blocking Probability in Cognitive Radio - Katta, Srinivas; Siva Ganga Prasad, M; T.P Madhav, B (International Journal of Engineering and Technology, 2018)
We consider Teaching Learning Based Optimization (TLBO) to optimize the sensing error probability, Throughput and Blocking Probability in Cognitive Radio (CR) network. Sensing error probability, Throughput can be optimized by finding the optimal values of false alarm probability and detection probability. Blocking Probability can be optimized by finding the optimum value of number of guard channels. Results of TLBO are compared with Genetic Algorithm (GA) and Differential Evolution (DE) algorithm.Â Â